Exploring the Role of Semantic Metaphors Trough Whatsapp Chat in Daily Communication - Olivia Damanik; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
Abstract This study explores the presence and function of semantic metaphors in everyday WhatsApp conversations, drawing upon Conceptual Metaphor Theory (CMT) developed by Lakoff and Johnson. It investigates how abstract domains such as emotions, relationships, identity, and social dynamics are expressed through metaphorical language in informal digital interactions. Utilizing a qualitative approach, the research analyzes chat data collected from real-life conversations, categorizing metaphors into structural, orientational, and ontological types. The findings reveal that metaphorical expressions are not only pervasive but serve significant cognitive and communicative functions. They help users express complex emotions, negotiate social relationships, simplify abstract concepts, and reflect cultural values. The analysis demonstrates that WhatsApp, as a platform for spontaneous digital discourse, offers rich insight into how metaphor shapes meaning in modern communication. The study also emphasizes that metaphors in digital language are not merely rhetorical flourishes but central tools of cognition, identity construction, and interpersonal expression in contemporary society.